The Therapeutic Efficacy of Adipose Tissue-Derived Mesenchymal Stem Cell Conditioned Medium on Experimental Colitis Was Improved by the Serum From Colitis Rats - Qi, Li-li; Fan, Zhe-yu; Mao, Hai-guang; Wang, Jin-bo (Frontiers in Bioengineering and Biotechnology, 2021)
Adipose derived mesenchymal stem cells (AD-MSCs) have shown therapeutic potential in treatments of inflammatory bowel disease (IBD). Due to the harsh host environment and poor survival of the cells, controversy concerning the homing, proliferation and differentiation of MSCs in lesion tissue still remains. It has been reported that conditioned media from MSCs could improve the colitis, whereas the therapeutic efficiency could be significantly elevated by the stimulation of pro-cytokines. In this study, we pre-treated the adipose derived MSCs with the serum from colitis rats and then the activated conditioned media (CM-AcMSC) were collected. To compare the therapeutic effects of CM-MSC and CM-AcMSC on IBD, we constructed dextran sodium sulphate (DSS)-induced colitis rat models. The colitis was induced in rats by administrating 5% DSS in drinking water for 10 days, and the disease symptoms were recorded daily. The colon histopathological changes were observed by different staining methods (H&E and PAS). The expression levels of MUC2 and tight junctions (TJs) were determined by RT-qPCR. The levels of inflammatory cytokines were analyzed by ELISA and western blot analysis. Our findings suggested that CM-AcMSC was more effective in ameliorating the clinical features and histological damage scores. Treatment with CM-AcMSC significantly increased the expression of MUC2 and TJs and suppressed the production of pro-inflammatory cytokines in colonic tissues of colitis rats. The inhibitory effects of CM-AcMSC on inflammatory responses of colitis rats were mediated by NF-κB signaling pathway. These results suggested that pre-activation of MSCs with serum from colitis rats could promote the production of paracrine factors and improve the therapeutic effects of conditioned medium on colitis rats.